Direct Time‐Domain Observation of Conformational Relaxation in Gas‐Phase Cold Collisions. (15th March 2016) - Drayna, Garrett K.; Hallas, Christian; Wang, Kenneth; Domingos, Sergio R.; Eibenberger, Sandra; Doyle, John M.; Patterson, David
Abstract: Cooling molecules in the gas phase is important for precision spectroscopy, cold molecule physics, and physical chemistry. Measurements of conformational relaxation cross sections shed important light on potential energy surfaces and energy flow within a molecule. However, gas‐phase conformational cooling has not been previously observed directly. In this work, we directly observe conformational dynamics of 1, 2‐propanediol in cold (6 K) collisions with atomic helium using microwave spectroscopy and buffer‐gas cooling. Precise knowledge and control of the collisional environment in the buffer‐gas allows us to measure the absolute collision cross‐section for conformational relaxation. Several conformers of 1, 2‐propanediol are investigated and found to have relaxation cross‐sections with He ranging from σ=4.7(3.0)×10 −18 cm 2 to σ>5×10 −16 cm 2 . Our method is applicable to a broad class of molecules and could be used to provide information about the potential energy surfaces of previously uninvestigated molecules.